2021
DOI: 10.3390/ijerph182111146
|View full text |Cite
|
Sign up to set email alerts
|

High School Physical Education Teachers’ Perceptions of Blended Learning One Year after the Onset of the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has altered the educational landscape worldwide. One year after the disease outbreak, blended learning, which combines distance and face-to-face learning, became an alternative to fully online learning to address the demands of ensuring students’ health and education. Physical education teachers faced an additional challenge, given the experiential nature of their subject, but research on teachers’ perspectives is scarce. This study aims to explore high school physical education teachers’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 42 publications
0
20
0
1
Order By: Relevance
“…They ended up marking the period of confinement as an opportunity to learn other competences of the teaching profession, such as flexibility, adaptability, proactivity, creativity, knowledge, and handling of new digital tools. However, they also described that the essence of professional practice, which is based on contact and sensations associated with the corporeality provided by physical activity, did not allow for its full substitution by virtual reality [28,30,50,51]. The greatest difficulties for the teaching of Physical Education in the university context occurred in collective or group sports, such as basketball, volleyball, soccer, and handball, since it was impossible to carry out group body practices among students of the same level, which coincides with the results reported in the study by Bădău & Bădău [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They ended up marking the period of confinement as an opportunity to learn other competences of the teaching profession, such as flexibility, adaptability, proactivity, creativity, knowledge, and handling of new digital tools. However, they also described that the essence of professional practice, which is based on contact and sensations associated with the corporeality provided by physical activity, did not allow for its full substitution by virtual reality [28,30,50,51]. The greatest difficulties for the teaching of Physical Education in the university context occurred in collective or group sports, such as basketball, volleyball, soccer, and handball, since it was impossible to carry out group body practices among students of the same level, which coincides with the results reported in the study by Bădău & Bădău [56].…”
Section: Discussionmentioning
confidence: 99%
“…Considering this point of view, it could be said that teacher training in the field of Physical Education has been significantly affected by the changes brought about by the pandemic. These changes are due to its high content in practical modules, which has meant that teachers have to make methodological and didactic adjustments to comply with the disciplinary and pedagogical content that students in training must master so that they have the necessary skills for their future teaching practice [16,[28][29][30]. Likewise, Physical Education students have also had to face a totally different teaching-learning process, where all the practical subjects included in the curriculum have to be replaced by a virtual system.…”
Section: Introductionmentioning
confidence: 99%
“…Although using technology is considered as eliminating communication problems between teacher-student and student-student interaction, some educators participating in previous studies viewed limited communication as a barrier in using blended learning (Rasheed, Kamsin & Abdullah, 2020;Finlay, Tinnion & Simpson, 2022). As researchers reported that the challenges in the implementation of blended learning are workload because of crowded classes, work schedules and using various technology (Ibrahim & Ismail, 2021;López-Fernández, Burgueño, & Gil-Espinosa, 2021). The academicians stated that the most productive studies will be carried out in classes containing 20-30 students.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, Koekoek and van Hilvoorde (2018) thought over the need to understand the way teachers select digital technology, without losing educational goals. Further, this question becomes even more important due to the great use of digital technology in general, and particularly smartphone apps in PE to adapt the implementation of curriculum to the new instructional models derived from the COVID-19 pandemic (López-Fernández et al, 2021).…”
Section: The Current Research and Research Questionmentioning
confidence: 99%